Parasitic diseases in the practice of a pediatric multidisciplinary hospital - S. B. Chuelov; A. L. Rossina; T. M. Lebedeva; G. I. Volkova; Yu. N. Ivanova; D. V. Yerusalimskaya; S. A. Mustafayevа; O. V. Shamsheva (LLC "Diagnostics and Vaccines", 2020)
The experience of monitoring patients with parasitic diseases is presented. A brief literary reference is given and characteristics of patients hospitalized in the infectious-boxed department of a multidisciplinary hospital of federal subordination are given.Over the past 15 years, 22 children have been observed with parasitic diseases, including visceral toxocariasis - 11, visceral leishmaniasis - 5, diphyllobothriasis - 3, toxoplasmosis - 2, trichinosis - 1.Given the complexity of diagnosis and the possibility of developing life-threatening conditions in the absence of timely treatment, attention should be paid to a thorough collection of an epidemiological history, clinical and laboratory features of the course of human parasitoses, and laboratory diagnostic methods taking into account the life cycle of parasites.